Steel Stress Redistribution and Fatigue Life Estimation of Partially Prestressed Concrete Beams under Fatigue Loading. Issue 2 (February 2014) - Han, Jigang; Song, Yupu; Wang, Licheng; Song, Shide; Lei, Bing
The objective of this paper is to investigate the steel stress/strain variation and redistribution in partially prestressed concrete (PPC) post-tensioned T-beams with bonded tendons under various ranges of fatigue loading by using an embedded Fiber Bragg Grating (FBG) sensor. A total number of six beams were tested to failure under fatigue loading, and two control beams were tested for determing the monotonic bearing capacity. Test results indicated that the initial fatigue failure of all beams was caused by fatigue fracture of the non-prestressed reinforcement rather than failure of the prestressing strands. Based on the strain recorded, the development trends of non-prestressed steel strain and the ratio of strain range between prestressed and non-prestressed reinforcement during fatigue loading were described. Moreover, an analytical model for fatigue life prediction of partially prestressed concrete beams by using the sectional analysis and local strain-life method was developed. Good agreement between analytical and experimental results for fatigue life of PPC beams is observed.